2017
DOI: 10.1007/s10616-017-0068-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimized expression of the antimicrobial protein Gloverin from Galleria mellonella using stably transformed Drosophila melanogaster S2 cells

Abstract: Antimicrobial proteins and peptides (AMPs) are valuable as leads in the pharmaceutical industry for the development of novel anti-infective drugs. Here we describe the efficient heterologous expression and basic characterization of a Gloverin-family AMP derived from the greater wax moth Galleria mellonella. Highly productive single-cell clones prepared by limiting dilution achieved a 100% increase in productivity compared to the original polyclonal Drosophila melanogaster S2 cell line. Comprehensive screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 91 publications
2
21
0
Order By: Relevance
“…We used recombinant monoclonal D. melanogaster S2 cell lines expressing either gloverin from the greater wax moth Galleria mellonella (GmGlv) or BR021 from the harlequin ladybird Harmonia axyridis [ 30 , 32 , 33 ]. The genes encoding both antimicrobial peptides were controlled by the D. melanogaster metallothionein promoter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used recombinant monoclonal D. melanogaster S2 cell lines expressing either gloverin from the greater wax moth Galleria mellonella (GmGlv) or BR021 from the harlequin ladybird Harmonia axyridis [ 30 , 32 , 33 ]. The genes encoding both antimicrobial peptides were controlled by the D. melanogaster metallothionein promoter.…”
Section: Methodsmentioning
confidence: 99%
“…The optical density probe provides information about the number of light-scattering particles in the reactor. Both systems have been used separately to monitor processes based on lepidopteran cell lines and the lytic baculovirus expression vector system (BEVS) [ 11 , 26 , 27 , 28 ], but they have not been tested comprehensively with stably transformed Drosophila melanogaster S2 cell lines (rS2 cells), which provide an equally powerful expression platform [ 29 , 30 , 31 ]. We carried out an in-depth analysis of the ability of both methods to predict the density of rS2 cells during cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…We found that insects can selectively express AMPs and cytokine-like proteins when challenged with UPEC and ABU strains. For example, peptides with strong antibacterial activity, such as lysozymes, cecropins, gloverin, IMPI, galiomycin, and moricin, were strongly induced in the UPEC larvae (43)(44)(45)(46)(47)(48)(49), whereas anionic peptides and apolipophoricin, with weaker antimicrobial activity, were strongly induced in the ABU larvae. These data confirm that the ABU E. coli strain 83972 specifically downregulates AMPs with strong antibacterial activities to facilitate bacterial survival and prolonged infection in G. mellonella.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the production of an antimicrobial peptide (Gloverin-family), derived from the greater wax moth Galleria mellonella, we describe the efficient heterologous expression and basic characterization of the peptide (Zitzmann 2017). Thereby, a holistic strategy was pursued comprising optimizations on cellular and process level.…”
Section: Insect Biotechnologymentioning
confidence: 99%